Understanding the link between IS capabilities and cost performance in services: the mediating role of supplier integration. Issue 3 (10th June 2021) - Teng, Teng; Tsinopoulos, Christos
Abstract : Purpose: The purpose of this study is to explore the link between information systems (IS) capabilities, supplier integration and cost performance in the service context. Specifically, it empirically investigates how supplier integration meditates the relationship between three dimensions of IS capabilities and cost performance in service firms. Design/methodology/approach: A survey of 156 UK service firms was conducted and the data analyzed to determine the role of supplier integration in mediating the effects of IS capabilities on firms' cost performance. The research model was tested using structural equation modeling (SEM), and the neural network model was used to rank the relative influence of significant predictors obtained from SEM. Findings: The results confirmed that supplier integration fully mediates the effects of information technology (IT) for supply chain activities and flexible IT infrastructure on cost performance and partially mediates the effect of operations manager's IT knowledge on cost performance. The results showed that operations manager's IT knowledge is the strongest predictor of supplier integration. Originality/value: This study takes a step toward quelling concerns about the business value of IS, contributing to the development and validation of the measurement of IS capabilities in the service operations context. Additionally, it adds to the emerging body of literature linking supplier integration to the operational performance of service firms.